2010
DOI: 10.1007/s10530-010-9871-z
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity of introduced versus native purple loosestrife: univariate and multivariate reaction norm approaches

Abstract: The plastic responses to environmental change by Lythrum salicaria (purple loosestrife) were compared between native plants derived from seeds collected in Europe and those introduced into North America. Plants from nine populations each were grown under two levels of water and nutrient conditions. At the end of the growing season, samples were evaluated for eight traits related to their life history, plant size/architecture, and reproduction. Genetic (G), environmental (E), and G 9 E interactions were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Phenotypic plasticity is thought to be beneficial to founding populations by increasing niche breadth (e.g., Richards et al. , Chun , Davidson et al. ) or plasticity may be a trait that evolves in response to the novel environments (Richards et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenotypic plasticity is thought to be beneficial to founding populations by increasing niche breadth (e.g., Richards et al. , Chun , Davidson et al. ) or plasticity may be a trait that evolves in response to the novel environments (Richards et al.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic plasticity is thought to be beneficial to invaders because plastic “general‐purpose genotypes” could have a fitness advantage in founder populations (e.g., Richards et al. , Chun , Davidson et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By looking across both native and invasive ranges, some studies have demonstrated greater plasticity in invasive versus native populations for invaders such as Lythrum salicaria (Chun et al 2007;Chun 2011), Phalaris arundinacea (Lavergne and Molofsky 2007), and Senecio pterophorus (Cano et al 2008). However, other comparisons have not found strong differences in the plastic responses of native and invasive populations (Maron et al 2007;Bossdorf et al 2005;Andonian and Hierro 2011).…”
mentioning
confidence: 99%
“…In addition, phenotypic plasticity may arise in response to new selection pressures (eg extreme drought events) in a particular range of introductions (Hierro et al . 2005; Chun 2011). Under intense conditions, the individual musk thistle was exhibiting phenotypic plasticity, but its failure to flower and set seed likely meant it had not acquired the proper traits to successfully reproduce.…”
mentioning
confidence: 99%